METRICAL ESTIMATIONS OF DETERMINANT OF THE INTEGRAL PROBLEM FOR EQUATION OF VIBRATING OF STRING - Medvid, О. M.; Symotyuk, M. M.; Tymkiv, I. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2018)
Metrical theorems are inprocess set about estimations from below small denominators that arose up at investigational existence of periodic at times decision of task with integral conditions as moments after a spatial variable for equalization of small vibrating of string. For leading to of metrical estimations the concept of fractal measure and dimension of Hausdorff is from below applied.